Assessment of neuroactive steroids in cerebrospinal fluid comparing acute relapse and stable disease in relapsing-remitting multiple sclerosis. Issue 159 (May 2016) - Orefice, NS.; Carotenuto, A.; Mangone, G.; Bues, B.; Rehm, R.; Cerillo, I.; Saccà, F.; Calignano, A.; Orefice, G.
Highlights: Neuroactive steroids evaluation in male and female relapsing-remitting multiple sclerosis. Disease activity influences the neuroactive steroids metabolism in multiple sclerosis. More variations of neuroactive steroids metabolism in women than men multiple sclerosis. Increase of PREG and DHEA values in CSF of male and female relapsing-remitting multiple sclerosis. ALLO values significantly lower in female RR-MS patients. Abstract: Previous studies have reported an involvement of neuroactive steroids as neuroprotective and anti-inflammatory agents in neurological disorders such as multiple sclerosis (MS); an analysis of their profile during a specific clinical phase of MS is largely unknown. The pregnenolone (PREG), dehydroepiandrosterone (DHEA), and allopregnanolone (ALLO) profile was evaluated in cerebrospinal fluid (CSF) in relapsing-remitting multiple sclerosis (RR-MS) patients as well as those in patients affected by non-inflammatory neurological (control group I) and without neurological disorders (control group II). An increase of PREG and DHEA values was shown in CSF of male and female RR-MS patients compared to those observed in both control groups. The ALLO values were significantly lower in female RR-MS patients than those found in male RR-MS patients and in female without neurological disorder. During the clinical relapse, we observed female RR-MS patients showing significantly increased PREG values compared to female RR-MS patients in stable phase, while their ALLO values showed a significant decrease compared to male RR-MS patients of the same group. Male RR-MS patients with gadolinium-enhanced lesions showed PREG and DHEA values higher than those found in female RR-MS patients with gadolinium-enhanced lesions. Similary, male RR-MS patients with gadolinium-enhanced lesions showed PREG and DHEA values higher than male without gadolinium-enhanced lesions. Female RR-MS patients with gadolinium-enhanced lesions showed DHEA values higher than those found in female RR-MS patients with gadolinium-enhanced lesions. Male and female RR-MS patients with gadolinium-enhanced lesions showed ALLO values higher than those found in respective gender groups without gadolinium-enhanced lesions. ALLO values were lower in male than in female RR-MS patients without gadolinium-enhanced lesions. Considering the pharmacological properties of neuroactive steroids and the observation that neurological disorders influence their concentrations, these endogenous compounds may have an important role as prognostic factors of the disease and used as markers of MS activity such as relapses.